2023
DOI: 10.1142/s0217984923500409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geometric parameters on optical absorption characteristics of InGaN nanostructured arrays

Abstract: In recent years, with the development of wide-spectrum response photodetectors, InGaN as a semiconducting material has been widely studied. The nanowire array structure has excellent trapping ability, but different structures and shapes have different absorption abilities. It is necessary to optimize the nanowire array continuously in order to obtain the highest absorption efficiency possible. Based on this background, we study the effects of the geometry and structural parameters of InGaN nanowires on the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…These are mainly attributed to the trapping effect of nanostructures. 21,22 Zhangyang et al Under bias voltage, it can achieve a photocurrent efficiency of 13.75%, which is much higher than in previous reports. 24 Chen et al successfully grew InGaN NWA on the inclined pyramid substrate.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…These are mainly attributed to the trapping effect of nanostructures. 21,22 Zhangyang et al Under bias voltage, it can achieve a photocurrent efficiency of 13.75%, which is much higher than in previous reports. 24 Chen et al successfully grew InGaN NWA on the inclined pyramid substrate.…”
Section: Introductionmentioning
confidence: 72%
“…In order to absorb solar energy as high as possible, nanostructures of different shapes have been continuously developed. More and more research results have shown that InGaN nanostructures can achieve higher incident light absorption through antireflection. These are mainly attributed to the trapping effect of nanostructures. , Zhangyang et al used first-principles to calculate the electrical and optical properties of InGaN NWA structures under different In components. They found that NWs have better light absorption compared to thin film structures.…”
Section: Introductionmentioning
confidence: 99%